Mortality of Pelicans in the Shores of the Littoral of La Libertad (Perú) from a April to May 2012 (Journal of Namibian Studies : History Politics Culture, 2023)
It describes and analyzes the causes of massive mortality of Pelican (Pelecanus thagus), occurred on the beaches of the Region of La Libertad (Peru) during the months of April and May 2012. The research was carried out through a census of dead birds, dying ones and watching migrating flocks, also samples of digestive tracts were taken from 20 individuals dying in order to determine food habit, and body condition (previously total weight and total length were recorded). The results showed that the cause of mortality of 200 pelicans was the absence of their preferred food (anchovy), as well the thermal anomaly conditions of sea surface waters (temperatures above 18 ºC) caused the birds to migrate to cooler waters to south or deepen. It was determined that the birds had a high-level parasitism and low body condition, which is explained by starvation.